Magnetically separable Nd and Mn co-doped SrFe12O19 hexa-ferrites nanostructures for the evaluation of structural, magnetic and photo-catalytic studies under solar irradiation for the crystal violet dye removal from the industrial wastes. Issue 10 (15th May 2023) - Bibi, Firdous; Iqbal, Shahid; Kalsoom, Ambreen; Jamshaid, Muhammad; Ahmed, Adeel; Mirza, Misbah; Qureshi, Waseem Akhtar
Abstract: In the current research study, Nd & Mn co-doped strontium hexa-ferrite Sr1-x Ndx Fe12-y Mny O19 nanoparticles (NPs) were fabricated using facile micro-emulsion approach. The as-fabricated bare and co-doped materials were characterized for the structural X-ray diffraction (XRD), Raman and Fourier Transform of Infrared (FTIR), magnetic and photo-catalytic activities (PCA). The structural characterization confirms the synthesis of single phase M-type Sr-hexa-ferrite, along with successful doping of Nd and Mn ions at tetrahedral/octahedral site. The crystallite/grain size was observed to increase from 18 to 27 nm. The vibrating sample magnetometer (VSM) analysis revealed that the saturation magnetization (Ms), coersivity (Hc) and remanence increases on co-doping. Optical and band gap studies revealed the narrowing of energy band-gap (Eg ) which decreases from (2.18 eV–1.98 eV) on Nd and Mn doping which might be attributed to the new energy level generation in the co-doped materials. BET surface analysis shows well porous nature of the Nd and Mn co-doped materials with pore size 74 m 2 /g in comparison to 56 m 2 /g of un-doped material. The PCA was determined by solar-light degradation of crystal violet (CV) dye as industrial model contaminant. The results revealed that Nd and Mn co-doped Sr1-x Ndx Fe12-y Mny O19 NPs efficiently degraded CV dye (90.7%) when compared with (36.8%) of un-doped SrFe12 O19 NPs in the 90 min of solar-light exposure. This increase in the PCA was ascribed because of the narrow band gap and defected structure of Nd and Mn co-doped Sr1-x Ndx Fe12-y Mny O19 NPs. The stability and reusability tests revealed the excellent stability of the photo-catalyst which is only 1.10% loss observed after 5 repeated rounds which indicate its potential stability and reuse. The results of the application studies of Nd and Mn co-doped Sr1-x Ndx Fe12-y Mny O19 NPs revealed the potential uses for various electrical, as magnetic materials and for the remediation of toxic contaminants from the various industrial units and environment.